Microarray studies on the effect of silencing tynA in Escherichia coli K-12 - Heli Elovaara (Genomics Data, 2016)
To study the biological role of the tynA gene product of Escherichia coli, a primary amine oxidase (ECAO, E.C. 1.4.3.21), the tynA gene was genetically silenced by conjugation with a kanamycin resistance cassette. We used a microarray method to compare the mRNA expression in the modified strain (ΔtynA) to that in the wild type (wt) strain at the time of induction of ECAO expression (0 h) as well as 1 h and 4 h after the induction. These data in brief describe the different experimental conditions, sample preparation, data collection and analysis of the conducted microarray experiment. The differential expression of genes in the studied strains 1 h after the induction of ECAO expression is described. The microarray data have been deposited in NCBI's Gene Expression Omnibus and are accessible through GEO Series accession number GSE65385. Keywords: Escherichia coli, tynA, Primary amine oxidase, Microarray, ECAO